Sistem Pakar Diagnosa Kerusakan Notebook Berbasis Web Menggunakan Metode Certainty Factor dengan Pengujian Blackbox - Riston Burju Jordan Simatupang; Nur Nawaningtyas Pusparini (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
An expert system is a computer program designed to imitate the decision-making ability of an expert in a particular field, combining knowledge and rules obtained from experts to diagnose problems, provide advice, or make complex decisions, especially in notebook damage, so this requires the design of an expert system application for diagnosing notebook damage based on a website for users who support the diagnosis process using the certainty factor method, in terms of explaining the certainty factor which has a concept based on symptoms and diagnoses from the weight of an expert's value and the user's value, then calculated using the formula in CF, the final result is the creation of a website-based notebook damage diagnosis expert system.